Cambios semánticos en el léxico lunqu del anexo de Tuctumpaya - Farfán Cayllahua, Yazmine (2020)
The Lunqu lexicon is spoken by the Lunqus ‘peasants’ of the Arequipa countryside and, as it is a special language, it is only understood by them. This lexicon is influenced by Amerindian languages, both Quechua and Aymara, but in this paper, we only study those entries borrowed from Quechua and that keep the base word intact. Since the selected words show changes in their semantic information, the characteristic semantic features of the word are shown and a brief explanation about the semantic change produced in that lexicon is given.